Auditoría financiera a los estados financieros de la cooperativa de ahorro y crédito Cacec Ltda. del cantón Latacunga provincia de Cotopaxi período 2009 - Altamirano Albarracín, Marco Rodrigo (2011)
The mains objective of this research is the application of a financial audit of the Savings and Credit Cooperative Ltd. CACEC the same as possible to determine the degree of fairness of financial statements for a correct decision-making thus facilitating the lack of supervision and management control in the accounts, the methods used for the collection of information was the survey, interview, observation and audit methodology through which significant results were obtained by observing the positive and negative within the entity.